2023
DOI: 10.5194/tc-17-157-2023
|View full text |Cite
|
Sign up to set email alerts
|

Glaciological history and structural evolution of the Shackleton Ice Shelf system, East Antarctica, over the past 60 years

Abstract: Abstract. The discovery of Antarctica's deepest subglacial trough beneath the Denman Glacier, combined with high rates of basal melt at the grounding line, has caused significant concern over its vulnerability to retreat. Recent attention has therefore been focusing on understanding the controls driving Denman Glacier's dynamic evolution. Here we consider the Shackleton system, comprised of the Shackleton Ice Shelf, Denman Glacier, and the adjacent Scott, Northcliff, Roscoe and Apfel glaciers, about which almo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…This more than 50 m of thinning over 15 years is consistent with estimated basal melt rates 41 (Extended Data Figure 6) which were variable but averaged positive (melting) between 1992-2002, negative 2003-2013, and positive 2013-2018, suggesting less thinning during the middle period. Overall however, since ~2011, melt rates have increased, implying an increase in ocean temperature 42 , consistent with observations at neighboring SIS 43,44 . Between 2019-2021, ICESat-2 provided high-resolution along-track sampling, illuminating feature-level details of ice shelf topography 45,46 (Extended Data Fig.…”
Section: Changes In Elevation and Velocity Over The Cgis Systemsupporting
confidence: 83%
“…This more than 50 m of thinning over 15 years is consistent with estimated basal melt rates 41 (Extended Data Figure 6) which were variable but averaged positive (melting) between 1992-2002, negative 2003-2013, and positive 2013-2018, suggesting less thinning during the middle period. Overall however, since ~2011, melt rates have increased, implying an increase in ocean temperature 42 , consistent with observations at neighboring SIS 43,44 . Between 2019-2021, ICESat-2 provided high-resolution along-track sampling, illuminating feature-level details of ice shelf topography 45,46 (Extended Data Fig.…”
Section: Changes In Elevation and Velocity Over The Cgis Systemsupporting
confidence: 83%
“…Modeling work along the Totten Glacier showed that freshwater input from ice shelf melting was enough to offset the salt flux from sea ice production, preventing top‐to‐bottom convection (Silvano et al., 2018). Given there were no significant changes in the icescape of the Shackleton‐Denman System in the last 60 years (S. S. Thompson et al., 2023) or in the activity of the Shackleton Polynya (sea ice production increases 0.09% per year from 1992 to 2013; Tamura et al., 2016), it seems the freshening of DSW is more likely the result of melting (and thinning; Paolo et al., 2015) of the SIS.…”
Section: Discussionmentioning
confidence: 99%
“…East of the SIS (97-102°E), mCDW is not present near the ice front, with the exception of one profile that shows cold mCDW at the edge of the Scott Glacier. Given the calving front of the Scott Glacier advanced about 10 km from 1962 to 1991 before retreating back to the same position it was in 1962 in recent years (S. S. Thompson et al, 2023), this profile was likely to be near the ice front rather than underneath it, as Figures 2 and 3 might suggest. Data from the east of the SIS are limited though, and mostly sampled in shallower areas, meaning the possibility of a wider presence of mCDW, especially at depth, should not be discarded.…”
Section: Historical Datamentioning
confidence: 95%
See 1 more Smart Citation
“…The rapid acceleration of the Brunt Ice Shelf following calving represents a departure from the typical behaviour observed for this ice shelf over the last sixty years. Velocities of this magnitude are usually only measured on the ice shelves fed by exceptionally fast flowing outlet glaciers such as Thwaites, Pine Island and Denman Glaciers (Miles et al, 2020;Thompson et al, 2023). The Brunt Ice Shelf does not have a fast-flowing outlet glacier feeding it and under high velocities it is not fully replenished by ice from the continental interior.…”
Section: Discussionmentioning
confidence: 99%